State of Perception and Knowledge of Bioeconomy in Selected European Universities - Niewiadomski, Michał; Santamarta Cerezal, Juan C.; Tamáš, Vojtěch; dos Santos Pereira, Fernanda (De Gruyter Open Ltd., 2023)
Sustainable bioeconomy is one of the concepts that makes it possible to achieve the European Green Deal. A similar understanding of the term bioeconomy gives the opportunity to simultaneously take proportionate actions leading to the implementation of the Sustainable Development Goals in EU countries. Parallel understanding of the concept of bioeconomy is crucial for achieving a common consensus on actions aimed at introducing optimal plans for the development of green technologies. Therefore, the goal of the paper was to compare knowledge and perception about the bioeconomy in different countries. Realization of the work's objective was possible thanks to the use of the C&RT classification tree method. It was shown that the level of knowledge of respondents working or studying at selected universities was similar, while their perception of the bioeconomy differed significantly.
Keywords: bioeconomy knowledge; bioeconomy perception; circular economy; sustainable economy